Adolescent Women Marriage Practices and Peer Pressures in Rural West Java - Dhevi Pradipta, Novitha Syari; Sri Wahyuni, Ekawati; Sumarti, Titik (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTAdolescent marriage practices not only involve the structure in family or society but also related to the inter-individual social relations, one of them is peers. Peers are agent in the adolescent women marriage practices, because peers become a reference in act and behave for teenagers. The aim of this study are identify the peer pressures and analyze the agent’s actions of peers in adolescent women marriage practices. This research uses mixed-method that combines qualitative and quantitative. The results show that peers put pressures on three things related to adolescent women marriage practices in Gunungsindur village. Peers become one of the agents in adolescent women marriage practices. Peer’s actions are influenced by existing structures in society as well as by agency. Furthermore, the actions undertaken by peers or adolescent women actually perpetuate adolescent women marriage practices.Keywords: Adolescent marriage, agency, agent, peers, peer pressuresABSTRAKPraktik pernikahan remaja tidak hanya melibatkan struktur sosial tetapi juga berkaitan dengan relasi antar individu, salah satunya adalah teman sebaya. Teman sebaya merupakan agen dalam praktik pernikahan remaja perempuan, tindakan dan perilaku remaja termasuk remaja perempuan mengacu pada teman sebayanya. Tujuan penelitian ini adalah mengidentifikasi tekanan yang diberikan oleh teman sebaya dan menganalisis tindakan agen yaitu teman sebaya dalam praktik pernikahan remaja perempuan. Penelitian ini menggunakan pendekatan kuantitatif dan kualitatif melalui metode campuran. Penelitian ini menunjukkan bahwa teman sebaya memberikan tekanan dalam tiga hal terkait dengan praktik pernikahan remaja perempuan di Desa Gunungsindur. Teman sebaya menjadi salah satu agen dalam praktik pernikahan remaja perempuan Desa Gunungsindur. Tindakan yang dilakukan oleh teman sebaya dipengaruhi oleh struktur yang ada di masyarakat dan juga oleh agensi. Selanjutnya tindakan yang dilakukan oleh teman sebaya maupun remaja perempuan justru melanggengkan praktik pernikahan remaja perempuan.Kata kunci: Pernikahan remaja, agensi, agen, teman sebaya, tekanan teman sebaya